Utilizing Blockchain Technology to Modernize Police Operations: Ensuring Security, Transparency, and Efficiency - Feltovic, Milan (Eximia, 2024)
This article explores the transformative potential of blockchain technology in police operations, focusing on enhancing security, transparency, and efficiency. Initially recognized for its role in cryptocurrencies, blockchain's inherent immutability and distributed ledger features are now being leveraged to revolutionize data management within law enforcement. The technology ensures the secure, auditable, and tamper-resistant recording of all transactions and data related to police operations, from investigation records to evidence management, ensuring accessibility only to authorized personnel. Key areas examined include the enhancement of security and transparency through blockchain's immutable and distributed records, ensuring data integrity and evidence management by providing an unalterable record of all transactions and data, and improving interoperability among various police departments and agencies. The integration of advanced technologies like Zero-Knowledge Proofs and Layer 2 solutions further strengthens privacy protection and operational speed, contributing to a more efficient and reliable police information system. Practical implementations in police departments worldwide, such as Delhi Police's blockchain initiative for evidence tracking and Dubai Police's collaboration with Cardano Blockchain for secure data sharing, demonstrate significant improvements in transparency, integrity, and security of processes. The article concludes by addressing the ongoing challenges of scalability, interoperability, and privacy, emphasizing the need for continued development and standardization to fully realize blockchain's benefits in modernizing police operations. By evaluating these aspects, the article highlights blockchain's critical role in the digital transformation of law enforcement, promoting greater public trust and cooperation among police units at both national and international levels.